Observations of extremely metal-poor O stars: weak winds and constraints for evolution models - Telford, Grace; Chisholm, John; Sander, Andreas A. C.; Ramachandran, Varsha; McQuinn, Kristen B. W.; Berg, Danielle A. (The astrophysical journal, 2024)
Metal-poor massive stars drive the evolution of low-mass galaxies, both locally and at high redshift. However, quantifying the feedback they impart to their local surroundings remains uncertain because models of stellar evolution, mass loss, and ionizing spectra are unconstrained by observations below 20% solar metallicity (Z ⊙). We present new Keck Cosmic Web Imager optical spectroscopy of three O-type stars in the nearby dwarf galaxies Leo P, Sextans A, and WLM, which have gas-phase oxygen abundances of 3%-14% Z ⊙. To characterize their fundamental stellar properties and radiation-driven winds, we fit PoWR atmosphere models to the optical spectra simultaneously with Hubble Space Telescope far-ultraviolet (FUV) spectra and multiwavelength photometry. We find that all three stars have effective temperatures consistent with their spectral types and surface gravities typical of main-sequence dwarf stars. Yet, the combination of those inferred parameters and luminosity for the two lower-Z stars is not reproduced by stellar evolution models, even those that include rotation or binary interactions. The scenario of multiple-star systems is difficult to reconcile with all available data, suggesting that these observations pose a challenge to current evolution models. We highlight the importance of validating the relationship between stellar mass, temperature, and luminosity at very low Z for accurate estimates of ionizing photon production and spectral hardness. Finally, all three stars’ FUV wind profiles reveal low mass-loss rates and terminal wind velocities in tension with expectations from widely adopted radiation-driven wind models. These results provide empirical benchmarks for future development of mass-loss and evolution models for metal-poor stellar populations.